PENERAPAN PENDEKATAN STEM PROJECT BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR KIMIA - Riskayanti, Yunita (Prosiding Temu Ilmiah Nasional Guru, 2023)
The challenge for teachers is how to prepare appropriate learning designs as teaching innovations in order to create effective learning during the Covid-19 pandemic. Implementing online learning from home can reduce students' interest in learning. This shows that the learning process that has been implemented is not optimal, learning only occurs in one direction, there is no feedback from students, apart from that, distance learning makes it difficult for teachers to monitor students' learning progress. The aim of this research is to determine the effect of applying the STEM project based learning (PjBL) approach to improving chemistry learning outcomes during the Covid-19 pandemic. This research method is a quantitative method. Data collection techniques for learning outcomes consist of cognitive, psychomotor and affective domains. After implementing the STEM project based learning (PjBL) approach, the results of the attitude assessment consisting of the results of observing attitudes in class and the results of assessments between peers achieved an average of 95 excellent predicates. Learning outcomes increased, 31 students got a complete score and 2 students did not complete or 94% complete, the average learning outcome score was 87 with a good predicate. Based on the research results, it can be concluded that the application of the STEM project based learning (PjBL) approach can improve chemistry learning outcomes.